Principes, modalités et enjeux de l'évaluation des activités des professeurs d'université au Québec - Jean Bernatchez (Université de Provence, 2009)
This article aims to present the principles (why) and methods (how) of the evaluation of the activities of university professors in Québec, using as points of reference the three missions of the university : teaching, research, and community service. Our paper is organized around generic questions inspired by Abernot (1996). First, we present the context having contributed to the formalization of the evaluation of the activities. In conclusion, we illustrate some of the possible impacts. These evaluations contribute to increased quality, relevance and efficiency of the professors' activities in Québec. However, these concepts are not neutral and increasingly concord with the expressed desire to better serve the interests of the world market.